Lysozyme amyloid fibrils /tannic acid antibacterial nanohydrogels with interpenetrating polymer network structure: Synthesis, performance and mechanisms - Jinlu Zhang; Zhishuang Ma; Dongjie Liu; Mengxiao Yang; Aiqing Zhao; Runguang Zhang; Xinbing Yang; Dehui Lin (Food Research International, 2026)

Tailored high internal phase emulsion-filled/emulsion particulate gels based on gelatin/agar by cold gelation: stability, rheological behaviors, and delivery properties - Fengrui Zhang; Zhishuang Ma; Junqi Han; Xingbin Yang; Dehui Lin (Food Hydrocolloids, 2026)

Synergistic MOF-on-MOF S-scheme heterojunction for highly efficient peroxomonosulfate activation toward tetracycline degradation - Weiyan Su; Huage Lin; Dehui Zhang; Jiaxiang Zong; Guangyu Wu; Weinan Xing (Environmental Research, 2026)

Corrigendum to “YOLOv8-MDN-tiny: A lightweight model for multi-scale disease detection of postharvest golden passion fruit” [Postharvest Biol. Technol. 219 (2025) 113281] - Dengjie Chen; Fan Lin; Caihua Lu; JunWei Zhuang; Hongjie Su; Dehui Zhang; Jincheng He (Postharvest Biology and Technology, 2026)

Retraction Note: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2026)

Injectable near-infrared–responsive silk fibroin nanocomposite hydrogel enabling spatiotemporally controlled photothermal chemotherapy - Ling-Chu Yang; Ching-Wen Hwang; Shao-Hsuan Tsao; Hsin-Yao Lin; Yunching Chen; Dehui Wan (Chemical Engineering Journal, 2026)

Melatonin Attenuates Spinal Cord Injury by Regulating Ferroptosis Through the Nrf2/HO-1/GPX4 Pathway - Zhengxi Yu; Dingwei Wu; Tengbin Shi; Dehui Chen; Hao Feng; Huina Chen; Hailin Lin; Lei Sun; Wenge Liu (Molecular Neurobiology, 2025)

From immunosuppression to immune reprogramming: is triptolide a potential “immune reset” agent in autoimmune diseases? - Dehui Yu; Hu Lin (Immunologic Research, 2025)

Mechanistic and practical insights into tetracycline degradation via 2D/2D N-doped biochar/carbon nitride-driven peroxymonosulfate activation: Toxicity mitigation and product analysis - Jiaxiang Zong; Dehui Zhang; Huage Lin; Guangyu Wu; Weinan Xing (Environmental Research, 2025)

Preparation of W/W emulsion gels based on chitosan and carboxymethyl cellulose via associative phase separation - Jinfeng Zhao; Dehui Lin; Runguang Zhang; Di Wang; Aiqing Zhao; Honglei Tian; Xingbin Yang (Food Hydrocolloids, 2025)

Role of the plum cuticle layer in influencing fruit texture and permeation during the salting process - Dongjie Liu; Haoyu Zhou; Hua Huang; Qin Wang; Dehui Lin; Shuxiang Liu; Wen Qin; Gengsheng Xiao (Food Chemistry, 2025)

YOLOv8-MDN-Tiny: A lightweight model for multi-scale disease detection of postharvest golden passion fruit - Dengjie Chen; Fan Lin; Caihua Lu; JunWei Zhuang; Hongjie Su; Dehui Zhang; Jincheng He (Postharvest Biology and Technology, 2025)

Current status and trends of illegal trade in hawksbill turtle products in Hainan Island, China - Xinyu Ji; Zhao Wang; Ting Zhang; Dehui Chen; Wenxiang Yang; Meimei Li; Haitao Shi; Liu Lin (Frontiers in Marine Science, 2024)
Introduction Illegal wildlife trade is among the most profitable illegal businesses worldwide. The hawksbill turtle ( Eretmochelys imbricata ), which has been listed as Critically Endangered on the IUCN Red List, has long been a prominent target of illegal wildlife trading worldwide, thus posing a substantial threat to its continued survival. In China, although Hainan Island is the largest trading area and the most important transit point for the illegal trade of hawksbill turtles, very few investigations of this trade have been conducted here. Methods In this study, from 2019 to 2020, we conducted field investigations to assess the extent of the illegal trade in hawksbill turtle products in nine cities on Hainan Island. Results Among the 878 shops surveyed in 2019, 157 shops (17.9%) sold hawksbill turtle products, totaling 6,208 pieces. In 2020, 122 shops (13.6%) of 895 surveyed shops sold such products, totaling 1,821 pieces. Thus, these findings indicate that the number of shops selling hawksbill turtle products and the total number of products sold declined in 2020. Among the surveyed cities, the highest levels of illegal trade in hawksbill turtle products were recorded in Haikou and Sanya, the capital city of Hainan and a renowned tourist city, respectively. Jewelry and craft shops were found to produce the most products, accounting for 98.0% of the shops surveyed. Accessories such as bracelets and necklaces accounted for the highest proportions of hawksbill turtle products, representing 72.5% and 92.9% of the total in 2019 and 2020, respectively. Discussion The observed decline in illegal trade in 2020 can be attributed to a combination of factors, including a strengthening of government law enforcement and supervision after the COVID-19 pandemic, a shift in illegal trade from offline to online activities, and a reduction in tourists. Law enforcement agencies should continue strict enforcement and supervision to effectively combat illegal trade, particularly in the key trading areas of Haikou and Sanya. Additionally, authorities should emphasize public education to increase awareness of wildlife conservation and relevant legislation. The findings of this study will serve as a vital reference for relevant law enforcement agencies, contributing to the effective combatting and prevention of the illegal hawksbill turtle trade in China.

Numerical and experimental study on designs and performances of multi-serpentine flow field with bend-area block for proton exchange membrane fuel cell - Peijian Lin; Guoling Zhang; Dehui Yang; Yang Zhao; Hongyu Wang; Guogang Yang; Shian Li; Juncai Sun (Fuel, 2024)

Nitrogen addition impacts on soil phosphorus transformations depending upon its influences on soil organic carbon and microbial biomass in temperate larch forests across northern China - Linlin Zheng; Qiong Zhao; Guigang Lin; Xin Hong; Dehui Zeng (CATENA, 2023)

Recognition of multivariate geochemical anomalies using a geologically-constrained variational autoencoder network with spectrum separable module – A case study in Shangluo District, China - Bo Zhao; Dehui Zhang; Panpan Tang; Xiaoyan Luo; Haoming Wan; Lin An (Applied Geochemistry, 2023)

Nanocellulose: An amazing nanomaterial with diverse applications in food science - Fengrui Zhang; Rui Shen; Nan Li; Xingbin Yang; Dehui Lin (Carbohydrate Polymers, 2023)

PH sensitive double-layered emulsions stabilized by bacterial cellulose nanofibers/soy protein isolate/chitosan complex enhanced the bioaccessibility of curcumin: In vitro study - Rui Shen; Xingbin Yang; Dehui Lin (Food Chemistry, 2023)

Size-specific particulate matter and outpatient visits for allergic conjunctivitis in children: a time-stratified case-crossover study in Guangzhou, China - Jin Zhou; Lijun Fan; Hualiang Lin; Dehui Zheng; Lihong Yang; Dan Zhuo; Jiayang Zhuoma; Huan Li; Shiyu Zhang; Zengliang Ruan (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2018)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

Prokaryotic expression of pathogenesis related protein 1 gene from Nicotiana benthamiana: antifungal activity and preparation of its polyclonal antibody - Feng Zhu; Moyun Xu; Shaodong Wang; Shudan Jia; Ping Zhang; Honghui Lin; Dehui Xi (Biotechnology Letters, 2012)

BAK1 and BKK1 in Arabidopsis thaliana confer reduced susceptibility to turnip crinkle virus - Hui Yang; Xiaoping Gou; Kai He; Dehui Xi; Junbo Du; Honghui Lin; Jia Li (European Journal of Plant Pathology, 2010)